Correlation With Duration And Depression In TB Patients In Rural Jaipur District (NIMS Hospital) - SWARN LATA PANCHAL (International Journal of Pharma and Bio Sciences, 2011)
600 patients of pulmonary TB were studied using Beck depressive inventory. Depression was observed in 82% in females. It was observed more among elderly age group (45-55) person and females, business class patients, Middle (Education), Married and those who have low income. No difference was observed with martial and religion. The severity of depression was related to the duration of illness, severity of disease and response to chemotherapy. Depression was present in 82% in females and 52.6% in male of freshly diagnosed patients. It decreased to 69.8% in those who responded favorably to, chemotherapy but those with persistently positive sputum had a significantly high percentage 64%.